Las marcas comerciales y los acuerdos formales. - Valverde Sánchez, Alejandra Aythana (2024)
This research project examines the relationship between brands and formal agreements in the Ecuadorian legal context. The main objective is to analyze the current legal framework, trademark registration procedures, requirements, and benefits of formal trademark protection agreements. Additionally, relevant cases will be investigated, and recommendations will be made to enhance brand management and protection in Ecuador. The study is based on a theoretical and practical approach, utilizing legal sources, academic literature, and relevant cases in the field of intellectual property in Ecuador. The relevant laws and regulations will be explored, along with trademark registration procedures and the authorities responsible for the protection of trademarks in the country. Furthermore, the protection and management of commercial trademarks in Ecuador are analyzed in detail, examining the scope of their protection, the rights and obligations of trademark holders, and the legal actions available in the event of trademark infringement. Additionally, the role of formal agreements in the protection of commercial trademarks is studied, identifying the types of agreements used in Ecuador, the requirements for their validity, as well as the benefits and limitations associated with their implementation. The methodology used in this research is based on a qualitative approach, starting with theoretical analysis and case studies. A comprehensive review of relevant legislation, regulations, and pertinent cases in the field of intellectual property in Ecuador will be conducted. Similarly, practical cases of trademark infringement and the application of formal agreements within the Ecuadorian legal context will be examined. Additionally, the way in which formal agreements operate in relation to coexistence among trademarks in the legal context will be explored, providing a strong foundation for enhancing intellectual property protection. Keywords: trademarks, registration, formal agreements.